2018
DOI: 10.29252/ijmr-050106
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Needlestick Injuries and Exposure to Blood and Body Fluids Among Iranian Healthcare Workers: A Systematic Review

Abstract: Injuries caused by needles and sharp and cutting objects include wounds, cuts, or abrasions caused by medical devices that may have already been contaminated with blood or other body fluids. 1 In most studies on injuries caused by needles and sharp objects, the injuries are introduced as an important occupational hazard for healthcare workers. 2,3 There are about thirty-five million healthcare workers in the world who make up 12% of the world labor force. 4 The Center for Disease Control and Prevention estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
(9 reference statements)
1
10
2
Order By: Relevance
“…This finding is also inconsistent with a study in Iran which reported the prevalence of exposures at 46.47% [55]. The variance could be due to the discrepancies in the study participants (service personnel, paramedics, and nursing students were included) [55], types of included studies (historical cohort study were included in Iranian review) [55], the type of healthcare facilities (in the present review we included HCWs from primary healthcare units), and socio-demographic factors [9]. Generally, the lifetime BBF exposure rate in this study (54.9%) seems to be very low when we compared with the annual BBF exposure rate 44%.…”
Section: Discussioncontrasting
confidence: 95%
“…This finding is also inconsistent with a study in Iran which reported the prevalence of exposures at 46.47% [55]. The variance could be due to the discrepancies in the study participants (service personnel, paramedics, and nursing students were included) [55], types of included studies (historical cohort study were included in Iranian review) [55], the type of healthcare facilities (in the present review we included HCWs from primary healthcare units), and socio-demographic factors [9]. Generally, the lifetime BBF exposure rate in this study (54.9%) seems to be very low when we compared with the annual BBF exposure rate 44%.…”
Section: Discussioncontrasting
confidence: 95%
“…The foremost reason for this variation may be due to study setting dissimilarities. This finding is also inconsistent with a study in Iran which reported the prevalence of exposures at 46.47% [56]. The variance could be due to the discrepancies in the study participants, the type of healthcare facilities, and socio-demographic factors.…”
Section: Discussioncontrasting
confidence: 81%
“…The lifetime prevalence range was slightly better than the finding from Pakistan (30 to 73%) [62]. Also, a systematic review from Iran has estimated the NSI prevalence to be between 10 and 84.3% [63]. This variation could be due to differences in awareness, training opportunity, degree of exposure to needles, availability, and utilization of protective devices recall bias and slight methodological differences among studies.…”
Section: Discussionmentioning
confidence: 84%